2016
DOI: 10.17577/ijertv5is020526
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Springback Variation in V Bending

Abstract: In order to get exact shape and size of components in sheet metal manufacturing, springback effect plays a pivotal role. Prediction of springback angle helps in determining the amount of over-bend (i.e. springback compensation) required so that exact V bend angle can be obtained in the component. In this study an attempt has been done to analyze the springback effect for simple V-bending operation performed on CRDQ (Cold Rolled Draw Quality) with thickness of sheet varying from 2.0 to 4.0 mm. In this work Hype… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 12 publications
0
1
0
Order By: Relevance
“…Upon forming spring-back will present always and cannot be eliminated but can be minimized by reducing elastic recovery of sheet metal with the help of suitable die design, and optimal setting of process parameters (Bakhshi-Jooybari et al 2009). To produce the parts with quality and economy, it is very important to take the spring-back into account and understand the bending mechanics to evaluate the spring-back and bending forces accurately (Gautam et al 2016). Deviation of shape and size upon forming the components causes rejection and hence it becomes essential to understand the spring-back phenomenon of the sheet metal components .…”
Section: Introductionmentioning
confidence: 99%
“…Upon forming spring-back will present always and cannot be eliminated but can be minimized by reducing elastic recovery of sheet metal with the help of suitable die design, and optimal setting of process parameters (Bakhshi-Jooybari et al 2009). To produce the parts with quality and economy, it is very important to take the spring-back into account and understand the bending mechanics to evaluate the spring-back and bending forces accurately (Gautam et al 2016). Deviation of shape and size upon forming the components causes rejection and hence it becomes essential to understand the spring-back phenomenon of the sheet metal components .…”
Section: Introductionmentioning
confidence: 99%
“…A numerical analysis of the bending process is yet another approach. The authors of [5] performed an FEM simulation of various thickness steel bending processes. It was confirmed that the value of the springback coefficient depends on the sheet thickness but it was demonstrated that after exceeding a certain critical value, further increase of sheet thickness again starts to have a negative effect.…”
Section: Introduction and Literature Surveymentioning
confidence: 99%